Effectiveness of vocational-to-bachelor continuation of studies: an inclusion mechanism for academic success in higher education - Jorge Miranda-Ossandón; Carla Muñoz; Jorge Valenzuela (Journal of Education and Learning (EduLearn), 2026)
In the context of promoting student inclusion in higher education, this study examines the effectiveness of transition programs from vocational to undergraduate education as access mechanisms that enable effective and successful inclusion. A cohort of 637 Chilean students from three academic disciplines, namely, agronomy, early childhood education, and physical education was analyzed, comparing academic performance, failure rates, and persistence between continuation program participants and students admitted through traditional or inclusive pathways. Statistical analyses, including persistence metrics and analysis of variance (ANOVA), indicate that students in the continuation program achieve equal or superior academic outcomes to their peers admitted through regular or other inclusionary pathways. These results provide evidence to support the relevance and feasibility of this type of higher education pathway access as an effective inclusive education strategy in terms of academic success and persistence. So, this paper contributes with specific evidence on the effectiveness of this inclusion mechanism, which could be relevant for designing efficient inclusion policy mechanisms. However, future studies that address career paths and professional development longitudinally must complement these initial results.